PEMANFAATAN MEDIA SOSIAL SEBAGAI SUMBER INFORMASI AWAL BAGI MAHASISWA ILMU KOMUNIKASI UINSU - Devin Lutfi Faturtama; Syahrul Abidin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The purpose of this qualitative study is to analyze the use of social media as a primary source of information by Communication Studies students at Islamic University of North Sumatra. We conducted interviews with these students to obtain relevant data. This study looks at the role of social media in providing information to students and the impact of extensive information on social media on students. Various types of content such as images, videos, and text are on social media and can influence student thinking. However, it is important for students with critical thinking skills to assess and evaluate the accuracy of information they find on social media. While using social media as a first source of information can be very beneficial for students, they also need to be able to select information that is relevant and helpful to them in addressing the challenges and problems they face.